A new species of Polypedates (Anura: Rhacophoridae) from Gunung Murud, Sarawak (Northwestern Borneo) - Das, I. (National University of Singapore, 2005)
A new species of rhacophorid of the genus Polypedates is described from Gunung Murud, Sarawak State, north-western Borneo. Polypedates chlorophthalmus, new species is compared with congeners from Borneo and other parts of southeast Asia. The new species is diagnosable in showing the following combination of characters: SVL 62.1 mm in the unique holotype; snout rounded, not projecting beyond mandible; head slightly wider than long; canthus rostralis sloping; no dermal flap along forearm; supracloacal fold absent; skin not co-ossified to cranial bones, median lingual process absent; supratympanic fold distinct; dorsum brown, with a thin dark gray line at back of forehead, nearly converging at the axilla, lacking dark lines; lower flanks and anterior edge of thighs with dark blotches; throat with dark pigmentation; and iris bright green.